2020
DOI: 10.7554/elife.53934
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule functional anatomy of endogenous HER2-HER3 heterodimers

Abstract: Human epidermal growth factor receptors (HERs) are the primary targets of many directed cancer therapies. However, the reason a specific dimer of HERs generates a stronger proliferative signal than other permutations remains unclear. Here, we used single-molecule immunoprecipitation to develop a biochemical assay for endogenously-formed, entire HER2-HER3 heterodimers. We observed unexpected, large conformational fluctuations in juxta-membrane and kinase domains of the HER2-HER3 heterodimer. Nevertheless, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…BCL2 proteins are membrane proteins with a single transmembrane domain (TMD) 43 . We then extracted the labeled BCL2 proteins using mild cholesterol-like detergents in a protocol proven to preserve membrane patches surrounding extracted membrane proteins 42 . Using anti-RFP antibodies over a layer of poly-ethylene glycol (PEG) polymers to minimize non-specific protein adsorption, we surface-immobilized the BCL2 proteins from crude cell lysates (Fig.…”
Section: Application Of Single-molecule Co-ip To the Bcl2 Ppi Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL2 proteins are membrane proteins with a single transmembrane domain (TMD) 43 . We then extracted the labeled BCL2 proteins using mild cholesterol-like detergents in a protocol proven to preserve membrane patches surrounding extracted membrane proteins 42 . Using anti-RFP antibodies over a layer of poly-ethylene glycol (PEG) polymers to minimize non-specific protein adsorption, we surface-immobilized the BCL2 proteins from crude cell lysates (Fig.…”
Section: Application Of Single-molecule Co-ip To the Bcl2 Ppi Networkmentioning
confidence: 99%
“…𝑉𝑉=measured normalized PPI, 𝑉𝑉 0 =fixed minimum PPI (typically 𝑉𝑉 0 = 0), 𝑉𝑉 𝑚𝑚𝑚𝑚𝑚𝑚 = maximal PPI, [𝐴𝐴𝐴𝐴𝐴𝐴]=concentration of ABT-199, [𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝]= concentration of prey proteins, 𝐾𝐾 𝑑𝑑 =fixed dissociation constant measured in equation (1), 𝐾𝐾 𝑖𝑖 =fitted inhibitory constants of ABT-199. Detection of fluorescence by TIR microscope and post-image analysis: All singlemolecule fluorescence signals were measured using the home-built objective-based TIR fluorescence microscope as pre-reported methods42 . For TIR illumination, the laser wavelength of 488 nm and 532 nm were used for eGFP and mCherry excitation respectively.The single-molecule fluorescence signal was detected via the electron-multiplying chargecoupled device (EMCCD) (iXon 897, DU-897U-CS0-EXF; ANDOR) for 10 frames (typically 100 ms exposure) and recorded in a TIFF stack file format.…”
mentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 (HER2) is often expressed in a variety of tumors tissues and is closely related to the development of carcinoma, while HER2 activates the downstream signaling pathways through heterodimer and tyrosine kinase autophosphorylation mediated signal transduction (De Santis et al., 2019 ; Akbari et al., 2020 ); and which gene magnification and protein overexpression play a crucial role in the cell proliferation, adhesion, aggressiveness apoptosis as well angiogenesis of numerous solid tumors (Kaur & Dasanu, 2011 ). In addition, HER-2 can also build heterodimers with the rest of the EGFR family and produce a marked effect in regulating tumor cell proliferation, differentiation, migration, and tumorigenesis (Rohlenova et al., 2016 ; Choi et al., 2020 ). Approximately 15–20% of gastric carcinoma/gastric and gastroesophageal junction carcinoma (GC/GEJC) and 12–23% of breast cancers (BC) overexpress HER2 (Study Group HER2 Monitor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, technical advancements from our group (3) and others (47) have begun to improve the potential of cell-based assays to yield quantitative information about protein complexes. A pioneering study from Jain and colleagues (4) showed that protein-protein interactions could be assayed in cell lysates by immunoprecipitating fluorescently tagged proteins onto microscope coverslips and imaging the resulting immunocomplexes using single-molecule TIRF microscopy, an approach termed si ngle- m olecule pull -down (SiMPull).…”
Section: Introductionmentioning
confidence: 99%
“…Because SiMPull counts individual protein complexes, it can provide a digital, quantitative measurement of the fraction of proteins in complex in a given sample. Subsequent work from the Yoon lab (6, 7) further developed this approach by pulling down a tagged protein and then adding a second cell lysate carrying a tagged binding partner; by monitoring these reactions over time, they were able to extract kinetic parameters describing the binding. However, the protein complexes studied in this approach were formed on the coverslip surface, and thus did not represent native cellular interactions (6).…”
Section: Introductionmentioning
confidence: 99%